2020
DOI: 10.1002/cam4.3301
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and prognosis of distant metastases in nasopharyngeal carcinoma: A large‐population retrospective analysis

Abstract: Currently, the features and prognosis of nasopharyngeal carcinoma (NPC) with distant metastases are still rarely reported. Thus, the main purpose of our study was to investigate the metastasis patterns of different histological types of NPC and to clarify the prognostic characteristics of metastases at different sites. Patients were enrolled from the SEER program from 2010 to 2016. Chi‐squared tests were used to compare features between groups. The tendency to develop combined metastases was assessed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…Chemotherapy at the IVC stage produced improved OS (HR: 0.41, 95% CI: 0.26-0.67, and P <0.001) but did not signi cantly affect CSS. Furthermore, chemotherapy was signi cantly associated with improved OS in this study, which was consistent with the researches mentioned, which reported that chemotherapy may improve the OS of old patients with de novo metastatic NPC [16,27]. Unfortunately, radiation was not found to be an independent prognostic factor and only improved OS.…”
Section: Survival Analysessupporting
confidence: 91%
See 1 more Smart Citation
“…Chemotherapy at the IVC stage produced improved OS (HR: 0.41, 95% CI: 0.26-0.67, and P <0.001) but did not signi cantly affect CSS. Furthermore, chemotherapy was signi cantly associated with improved OS in this study, which was consistent with the researches mentioned, which reported that chemotherapy may improve the OS of old patients with de novo metastatic NPC [16,27]. Unfortunately, radiation was not found to be an independent prognostic factor and only improved OS.…”
Section: Survival Analysessupporting
confidence: 91%
“…On the Kaplan-Meier survival curve, bone metastases demonstrated poor OS and CSS outcomes. However, Qu Weiling's study obtained opposite results, and meaningful results regarding CSS were obtained using a log-rank test for both liver and metastases [27]. Beyond these metastases, other metastatic sites and the number of metastatic organs may signi cantly affect survival.…”
Section: Survival Analysesmentioning
confidence: 95%
“…The N-stage, which remains the indispensable parameter of the current staging system, appears to reflect the locoregional aggressiveness and tendency for the development of DMs, and therefore, dismal prognosis in such patients. 25 The degree of weight loss in the past 6-months has been specified as one of the key measures to define cancer cachexia in both the Washington and Delphi consensus, respectively. 24 , 26 Additionally, our results confirm the recently published findings of a comprehensive study by Ou et al, who proposed the pretreatment percent weight loss as a vigorous prognostic marker after treatment in a group of 681 NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the proven effectiveness of radiotherapy and concurrent or adjuvant chemotherapy, about 30-40% of NPC patients still suffer from disease relapse after initial control [2]. It's extremely challenging to deal with relapsed NPC including loco-regional recurrence and distant metastasis, with death caused by distant metastasis alone can be as high as 62% [3]. Therefore, how to accurately stratify the risk of disease relapse in advance and individualize the treatment plan accordingly is highly desired in the new era of precision medicine, which would greatly further improve the overall prognosis.…”
Section: Introductionmentioning
confidence: 99%